Statistical Analysis of the Electric Car Market Development in Ukraine: Problems and Solutions - Honchar, I. A.; Palyan, Z. O. (Statistics of Ukraine, 2018)
UN Sustainable Development Goals contain an ecological component: stabilizing atmospheric concentrations of greenhouse gases and finding alternative sources of energy. The introduction of electric cars will help solve both problems simultaneously. The analysis of the current world trends in the cars market shows the steady growth of consumer preferences for electric cars and the rapid reaction of the world’s automakers. According to forecasts provided by Bloomberg New Energy Finance, it is expected that in 2040, more than half (54%) of world car sales will come from electric vehicles. The spread of this type of ecological vehicles associated with the decision on technical, organizational and legal nature create an infrastructure of electric charging stations. The article proposed analyzes the dynamics of prevalence of electric vehicles and development of services of electric charging stations in Ukraine. In the car market electric cars Ukraine appeared recently, since 2012 (the first 10 units), but during the next 5 years, the number of registered annually increased by 37.5 times and as of 01.01.2018 already numbered 5688 cars. The rapid increase in the number of registered electric vehicles started from 2016, when the import duty on electric cars was canceled at the legislative level. The number of registered electric cars in Ukraine increased by 11 times in 2016–2017. During these two years the share of electric cars in total sales doubled and reached 4.6% in 2017. Today the coverage of the territory of Ukraine by electric charging stations is about 20%. However, the rate of expansion of the number of electric charging stations even for one 2017 year are impressive, namely, the fourfold increase. Expansion of the Ukrainian market of electric cars is constrained by the unregulated status of electric charging stations, as well as services related to servicing and operation of electric vehicles. First of all, the issue of classification of the activity of providing services for charging the battery of electric cars should be solved. It is possible to resolve the issue, if one distinguishes a separate activity in one of the Classification of Economic Activities (CEA) sections. The current version of the Classification of Economic Activities contains an activity related exclusively to vehicle maintenance (section G, division 45, group 2), which does not include service for charging a car battery. The solution of the issue is the introduction of a new type of activity: “Services for charging batteries”. As a result it will allow creating favorable conditions for the development of the market for servicing and operation of electric vehicles.